Assessing future European lithium supply using a bottom-up approach - Månberger, André (The 38th International Electric Vehicle Symposium & Exhibition, Gothenburg, Sweden, 2025-06-15 - 2025-06-18, 2025)
EVs increase demand for critical raw materials (CRMs). Many of the CRMs are mined in just a handful of countries, raising security concerns among business and policymakers. Lithium is particularly precarious due to its high geographic supply concentration, high demand growth rate and few near term substitutes. This study conducts a bottom-up assessment of European lithium extraction projects. The study identifies 18 projects within Europe that could commence mining before 2030. If all of these would start as envisioned by the mining companies, the European lithium supply would amount to 346kt lithium carbonate equivalent (LCE). Many of the projects are costlier than international peers, making their financial viability sensitive to international prices. Also, some of the projects will likely be delayed or cancelled due to lack of permits, capital, new extraction technologies and social acceptance. Policymakers need to assess and prioritize the value of self-sufficiency compared to other societal goal